2015
DOI: 10.1016/j.beproc.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term test–retest reliability of delayed reward discounting in adolescents

Abstract: Delay discounting (DD), a decline in subjective value of a reward with increasing temporal delay in receipt of that reward, is an established behavioral indicator of impulsivity. Preference for smaller-immediate over larger-delayed rewards, has been implicated in the basic neurobehavioral mechanisms of risk for addictive disorders and related externalizing psychopathology. Establishing long-term stability of DD in adolescence is a necessary step towards its validation as an intermediate phenotype, or marker of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…The ln k of youth in this study (M ln k = −4.56, see Table 1) was similar to average discounting rates found in other samples of adolescents (Duckworth & Seligman, 2005; Stanger et al, 2012). In addition, research on this task in adolescents has shown good test-retest reliability during both middle and late adolescence (Anokhin, Golosheykin, & Mulligan, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The ln k of youth in this study (M ln k = −4.56, see Table 1) was similar to average discounting rates found in other samples of adolescents (Duckworth & Seligman, 2005; Stanger et al, 2012). In addition, research on this task in adolescents has shown good test-retest reliability during both middle and late adolescence (Anokhin, Golosheykin, & Mulligan, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Adolescents, relative to children and adults, demonstrate heightened responsivity to rewards across multiple measurement strategies including self-reports of BAS (Pagliaccio et al, in press), reward pursuit behaviors (Anokhin, Golosheykin, & Mulligan, 2015), and neural indices of reward processing (e.g., Forbes, Ryan, et al, 2010). This work has largely relied on cross-sectional studies; thus, additional longitudinal work is needed to further evaluate these trends.…”
Section: The Reward Systemmentioning
confidence: 99%
“…This is probably due to individual difference factors (such as future orientation and impulsivity), cognitive functioning (such as the ability to imagine and experience pleasure or pain in advance of future events), and the maturation of brain system during adolescence (Banich et al 2013). A recent study by Anokhin, Golosheykin, and Mulligan (2015) demonstrated that, in spite of the presence of systematic age-related changes from age 16 to 18 years, individual differences in delay discounting showed considerable stability over this period.…”
Section: Introductionmentioning
confidence: 99%